ANALISIS VEGETASI DAN ESTIMASI BIOMASSA STOK KARBON POHON PADA TUJUH HUTAN GUNUNG, SUAKA ALAM PULAU BAWEAN JAWA TIMUR - Trimanto Trimanto (BERITA BIOLOGI, 2014)
Bawean Island is one of the small islands in the northern province of East Java. The existence of a number of waterfalls, lakes and elevated plains indicates that the diversity of habitat types on the island is quite high. This research activity aims to determine the diversity and vegetation of tree and estimation of carbon stocks of tree in Bawean Island Nature Reserve. The study was conducted using transects and purposive sampling methods. Data were analyzed by calculating the importance value index and the Shannon-Winner diversity index. The study results showed that the vegetation of trees in the Nature Reserve and Wildlife of Bawean Island is high with the value of the Shannon Wiener index(H ') is hight (5.01). The results of the analysis of the tree vegetation is known that the highest IVI owned by Ficus variegata with an IVI of 36.4. Two other important species in the region is Irvingia malayana with an IVI of 21.1 and Myristica guatteriaefolia with an IVI of 16.4. The results of calculations of carbon stocks in Bawean Island Forest showed that the average carbon obtained was 150,71 ton C ha-1. The highest carbon stocks are Mount Kastoba forest and Lumut Mount Forest. Irvingia malayana is accounted for the largest carbon stocks (33.95 ton C ha-1).